Treatment of Post‐Inflammatory Hyperpigmentation in Patients With Darker Skin Types Using a Low Energy 1, 927 nm Non‐Ablative Fractional Laser: A Retrospective Photographic Review Analysis. Issue 1 (29th October 2019) - Bae, Yoon‐Soo Cindy; Rettig, Samantha; Weiss, Elliot; Bernstein, Leonard; Geronemus, Roy
Abstract : Background and Objectives: Post inflammatory hyperpigmentation (PIH) can be difficult to treat especially in patients with darker skin types as darker skin carries increased epidermal melanin content. Various treatments available to improve the appearance of PIH may incite further pigmentation thus making treatment extremely difficult and frustrating. The purpose of this study was to perform a retrospective chart and photographic review to evaluate the efficacy and safety profile of a low energy low density non‐ablative fractional1927 nm wavelength laser treatment for PIH in patients with Fitzpatrick skin types IV‐VI. Study Design: A retrospective evaluation of 61 patients with PIH treated with a 1927 nm laser was conducted at a single center. Inclusion criteria required at least 2 treatment sessions so that before and after treatment photographs would be available for comparison and study purposes. Two blinded physician‐evaluators using a visual analog scale for percentage of pigmentary clearance in standard photographs assessed treatment efficacy. Results: The mean percent improvement after treatment, evaluated by two dermatologists was 43.24%. The correlation between raters was statistically significant (Pearson's correlation coefficienct of r = 0.59, p < 0.0001). No side effects were observed in the patients treated with the 1927 nm laser. Conclusion: The low energy low density non‐ablative fractional 1927 nm wavelength laser is a safe and effective modality for improving post inflammatory hyperpigmentation in patients with darker skin types. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.